SECOND TIME PROJECT: GAME AS A TOOL TO MINIMIZE AGGRESSION OF A GROUP OF PUBLIC SCHOOL STUDENTS OF FORTALEZA. (Fiep Bulletin - online, 2016)
This study aims to determine the importance of play as a tool to minimize the aggressiveness of a group of public school students who participate in the Project Second Time in school. For this research field, we used a quantitative approach, being a descriptive study and interventionist type, the data were summarized and analysed from a survey and systematic observations during the implementation of project activities. This study found a beneficial contribution of cooperative games in decreased aggressiveness of students enrolled in the Second Half Project.
Keywords: cooperative games; design second half; aggressiveness.